2001
DOI: 10.1161/hc4601.099404
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Angiotensin II Type 2 Receptor Stimulation Associated With Selective Angiotensin II Type 1 Receptor Blockade With Valsartan in the Improvement of Inflammation-Induced Vascular Injury

Abstract: These results suggest that the stimulation of the AT(2) receptor after AT(1) blockade is important in the improvement of the inflammatory vascular injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
179
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(193 citation statements)
references
References 23 publications
5
179
1
1
Order By: Relevance
“…Accumulating evidence now shows that inflammatory cell infiltration [2,3], proliferation/migration of vascular smooth muscle cells (VSMCs) [4,5], and deposition of extracellular matrix [6] all contribute to the pathogenesis of neointimal hyperplasia. Moreover, inflammatory cell infiltration of the neointima is intimately related to oxidative stress [7], and several lines of evidence indicate that NADPH oxidase plays a crucial role in the production of reactive oxygen species (ROS) within the neointima [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence now shows that inflammatory cell infiltration [2,3], proliferation/migration of vascular smooth muscle cells (VSMCs) [4,5], and deposition of extracellular matrix [6] all contribute to the pathogenesis of neointimal hyperplasia. Moreover, inflammatory cell infiltration of the neointima is intimately related to oxidative stress [7], and several lines of evidence indicate that NADPH oxidase plays a crucial role in the production of reactive oxygen species (ROS) within the neointima [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent data show that cardiac c-Kit + AT2R + cell population exists and concerns adaptive cardioprotection (8), raising the importance of other potential cellular mechanisms, which may also contribute to AT2R-mediated repair processes in the heart. Several previous studies have suggested that Ang II via its AT1R plays an important role in triggering inflammatory cardiovascular injury (4,5). Indeed, the cardioprotective effects of AT1R blockade are related to reduced myocardial inflammation in patients with MI (9).…”
mentioning
confidence: 98%
“…A wealth of information indicates that the renin-angiotensin system can interfere with acute cardiac remodeling and inflammation processes during cardiovascular injury (4,5). Most of the cardiovascular actions of angiotensin II (Ang II), such as blood pressure and osmotic control, are mediated by AT1R (6).…”
mentioning
confidence: 99%
“…On the other hand, an angiotensin II type-1 receptor blocker (ARB), widely used as an antihypertensive drug, has been reported to have also antiatherosclerotic such as attenuating neointimal formation, decreasing vascular smooth muscle cell (VSMC) proliferation and diminishing vascular inflammation. 8 Considering these results, we hypothesized that an ARB has antiatherosclerotic effects via inhibiting TNF␣-RAGE interaction, thus leading to the decrease in the inflammatory process of atherosclerosis. We tested this hypothesis using human endothelial cells.…”
mentioning
confidence: 99%